Design, Development and Evaluation of Web Based Learning Management System - Ab. Aziz, Sidek (2007)
e-learning is a process of integrating Information and Communication Technology (ICT) into the learning system that can be used by users without the limitation of time and location. The e-learning framework application known as Learning Management System (LMS) is capable in managing the teaching and learning processes effectively. Lecturers use LMS for the intention of increasing and enhancing the teaching-learning environment for the students with the diversity of learning resources available on the internet sites. The goal of this research is to develop an LMS that suits the ICT competency of lecturers and students in UPM. Meanwhile, the objectives of this research are to identify the lecturers’ perception on the necessity in developing the LMS in order to inculcate the culture of e-learning as well as to assess its usage among lecturers and students. Hence a prototype LMS based on the Rapid Prototyping Design Model has been developed. Lecturers’ perceptions toward e-learning from the aspects of attitude, skills in technology as well as fields of expertise were examined to identify the lecturers’ need to use the LMS prototype. The research found that lecturers are positive towards new changes that are happening especially in the campus ICT development. Overall, it was found that respondents have quite a high perception towards attitude (mean=4.03, sd=.76), technology skills (mean=4.19, sd=0.85) and field of expertise (mean=4.07, sd=0.93). The respondents perception is also positive mainly about the needs of LMS (mean=4.12, sd=0.80) and Learning Contents Management System (mean=4.11, sd=0.80) in their efforts toward e-learning accomplishment. The LMS prototype adopting open source PERL as the programming language has been successfully developed in which it took into account the aspects of data flow, database design, process design, navigation and interface design. The web based application is used by the lecturers to organize the learning materials, whereby the student used it in order to access lecture notes; news updates of courses and to have online discussions. The interface design of the LMS prototype does not involve oversized graphic elements as it also has simple navigation to simplify the usage. The research on LMS prototype among students found that students enrolled in the course BIP3501 preferred the lectures notes module (72%), followed by the info/news updates module (15%) and tutorial activities (10%). On the other hand, students who enrolled for the course PHY4202, were more interested in accessing the info/news updates (40%), beside lectures notes (36%) and forum (22%). The difference in the pattern of preference for a particular module was apparently due to the learning method adapted for the course PHY4202 is more of Student Centered Learning (SCL) method while the course BIP3501 is more of Teacher Centered Learning (TCL) oriented. The lecturers’ perception towards the LMS prototype showed that they are really positive and agreed with the interface design and navigation with the mean score value excess of 3.50 for each item given. Respondents agreed with the LMS interface design that is simple with clear-cut text presentation (mean=4.10, sd=0.77), unambiguous icons or graphics (mean=4.14, sd=0.64), instructions that are easy to follow (mean=4.10, sd=0.68) and able to explore the LMS easily (mean=4.10, sd=0.79). The research also found that more than 40 lecturers (53%) who implemented SCL method updated the lectures notes at least once a week. The LMS prototype that has been developed fulfill the requirements of the users (mean=3.35, sd=0.93). For the purpose of organizing the learning resources through LMS, respondents also agreed that it is easy to upload (mean=3.69, sd=0.82) and to download (mean=3.70, sd=0.80) the teaching documents. In conclusion, respondents agreed that the LMS prototype which contains minimal modules is simple to be used (mean=4.04, sd=0.79) in accordance of the ICT competency of lecturers and students.